Rethinking modularity as contextual design thinking - Bramasta Putra Redyantanu; Rony Gunawan Sunaryo; Rony Gunawan Sunaryo (ARSNET, 2024)
This study aims to reflect and expand the notion of modularity in architectural design methods. The discussion about modular architecture is certainly familiar across architectural discourse; where its universality has been repeatedly challenged by the post-modern movement. The study aims to unpack and rethink the method and significance of modularity, not only as a means of repetition but as a contextual design response. The study generate reflection towards two lodge architecture design projects. The architecture of lodge provides complexities with regard to various programmatic needs, temporal occupation, quick construction processes, and often deep connection to the surrounding environment. This study examines four reflective concepts which expand the idea and method of modularity in architecture. First, the roof modules in lodge architecture promotes efficient spatial programs. Secondly, the use of modularity allows parallel operation of the building and the construction process. Thirdly, modularity enables construction of architecture as parts constructing the whole, creating connection between spatial scales. Fourth, modularity constructs the inside and outside experience, providing  connection with environmental context. This study offers a new perspective on repositioning and expanding modularity, not only as a means of repetition but also as a form of contextual design thinking.